REAKSI INVESTOR DALAM PASAR MODAL TERHADAP PERISTIWA AKSI BELA ISLAM 4 NOVEMBER 2016 DI JAKARTA (Studi Event Pada Perusahaan Yang Terdaftar Di LQ-45 Di Bursa Efek Indonesia) - Mutmainna Indah Andriyani Dewi; Mohammad Amin; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis research is conducted with the purpose of: 1) To know whether or notthere is a difference Return of stock before and last events of Islamic DefenseAction November 4, 2016 in Jakarta; 2) To know whether or not there is aTrade Volume Activity before and last event of Islamic Defense ActionNovember 4, 2016 in Jakarta.The population used in this research is all LQ-45 companies listed inIndonesia Stock Exchange (BEI) in 2016. The sample selection using purposivesampling. Based on the criteria, obtained 37 companies are samples in thisstudy. The method used in this study using the analysis method paired simple ttest.Based on the results of the analysis can be put forward several conclusions asfollows: 1) T test results show no significant difference between the returnbefore the incident of Islamic Defense Action 4 November2016 with after theevents of Islamic Defense Action November 4, 2016, this is held by thesignificance value t> 0, 05 ie 0.399; 2) There was no significant differencebetween TVA before the incident of Islamic Defense Action 4 November 2016with TVA after the events of the Islamic Defense Action 4 November2016. Thisis done by the significance value t> 0.05 that is 0,072.Keywords: Action to defend Islam 4 Nov 2016, TVA, Stock Return